Resident Workshop to Improve Inpatient Documentation Using the Progress Note Assessment and Plan Evaluation (PNAPE) Tool - Kirstin A. M. Nackers; Kristin A. Shadman; Michelle M. Kelly; Helen G. Waterman; Nicole L. Bentley; Daniel P. Gorski; Collette Chorney; Jens C. Eickhoff; Carrie L. Nacht; Daniel J. Sklansky (Association of American Medical Colleges, 2020)
Introduction Physicians enter residency with varied knowledge regarding the purpose of progress notes and proficiency writing them. The objective of this study was to test whether resident knowledge, beliefs, and confidence writing inpatient progress notes improved after a 2.5-hour workshop intervention. Methods An educational workshop and note assessment tool was constructed by resident and faculty stakeholders based on a review of literature and institutional best practices. The Progress Note Assessment and Plan Evaluation (PNAPE) tool was designed to assess adherence to best practices in the assessment and plan section of progress notes. Thirty-four residents from a midsized pediatric residency program attended the workshop, which consisted of didactics and small-group work evaluating sample notes using the PNAPE tool. Participants completed a four-question online pre- and postworkshop survey to evaluate their knowledge of progress note components and attitudes regarding note importance. Pre-post analysis was performed with Chi-square testing for true/false questions, and Mann-Whitney testing for Likert scale questions and summative scores. Results A majority of pediatric residents completed the preintervention (n = 26, 76% response rate) and postintervention (n = 23, 68% response rate) surveys. Accurate response rate improved in 15 of 20 of the true/false items, with a statistically significant improvement in five items. Resident perceptions of note importance and confidence in note writing also increased. Discussion A workshop intervention may effectively educate pediatric residents about progress note best practices. Further studies should assess the impact of the intervention on sustained knowledge and beliefs about progress notes and subsequent note quality.